Integrasi Pendidikan Kewirausahaan untuk Pengembangan Kreativitas dan Kesadaran Lingkungan Melalui PBA Kewirausahaan di Sekolah Dasar Muhammadiyah Perumnas - Ikbal Tawakka; Khairunnizha Khairunnizha; Jasri Jasri (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to increase students' creativity and environmental awareness through making bracelets from recycled beads at SD Perumnas Muhammadiyah. The activity began with an observation of the school environment to obtain an initial picture as a basis for planning. Students were involved in direct practice, starting from introducing materials, compiling designs, to the bracelet production process. The results of the activity showed the creation of 32 bracelets with 6 design variations. Although the average selling price was only IDR 7,000, lower than similar case studies (IDR 15,000), the increase in participants' skills reached 85%, exceeding the comparative study by 80%. Participants' environmental awareness also increased by 90%, indicating the success of the program in instilling ecological values. This activity not only hones technical skills, but also forms an attitude of responsibility, cooperation, and concern for the environment. This program is expected to be an example of good practice in developing character education and creativity in elementary schools.